Les pratiques de cartographie animée pour représenter le changement - Claire Cunty; Hélène Mathian; Groupe Cartomouv (M@ppemonde)
Animated maps have widely developed on the Web; animated maps are particularly suited for the representation of spatial and temporal phenomena. The production seems to follow no set rules, contrary to graphic semiology for static maps. In order to identify the choices made in cartographic representation and perhaps to ﬁnd common characteristics, this article oﬀers an interpretative framework to explore the conception of Web based maps. It starts with a presentation of the framework’s categories, illustrated by a corpus of diversiﬁed sites. Then, a summary is provided of this diversity.